2012
DOI: 10.1373/clinchem.2011.171637
|View full text |Cite
|
Sign up to set email alerts
|

Candidate Serum Biomarkers for Prostate Adenocarcinoma Identified by mRNA Differences in Prostate Tissue and Verified with Protein Measurements in Tissue and Blood

Abstract: BACKGROUND Improved tests are needed for detection and management of prostate cancer. We hypothesized that differential gene expression in prostate tissue could help identify candidate blood biomarkers for prostate cancer and that blood from men with advanced prostate disease could be used to verify their presence in circulation. METHODS Candidate markers were identified using mRNA expression patterns from laser-capture microdissected prostate tissue. Tissue expression was confirmed using immunohistochemistr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 29 publications
(30 reference statements)
3
49
0
Order By: Relevance
“…ASPN, a new member of the SLRPs, is expressed abundantly in several malignant tumors, suggesting its involvement in the tumorigenesis and progression of cancer (6). Our present results, consistent with previous studies, revealed a significantly elevated ASPN expression in carcinoma tissues relative to the matched adjacent non-tumor tissues (11)(12)(13)(14). In addition, ASPN had varied expression in an inverse trend according to the differentiation degree of gastric cancer epithelial cell lines, hinting its oncogenic property, to some extent.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…ASPN, a new member of the SLRPs, is expressed abundantly in several malignant tumors, suggesting its involvement in the tumorigenesis and progression of cancer (6). Our present results, consistent with previous studies, revealed a significantly elevated ASPN expression in carcinoma tissues relative to the matched adjacent non-tumor tissues (11)(12)(13)(14). In addition, ASPN had varied expression in an inverse trend according to the differentiation degree of gastric cancer epithelial cell lines, hinting its oncogenic property, to some extent.…”
Section: Discussionsupporting
confidence: 92%
“…Particularly, Satoyoshi et al recently concluded that ASPN activates the coordinated invasion of scirrhous gastric cancer and cancer-associated fibroblasts by activation of the CD44-Rac1 pathway (7). In addition, by applying quantitative mass spectrometry, innovative proteomic technologies or microarray analysis, ASPN was proven to be upregulated in a series of cancers, including pancreatic cancer (11), pancreatic ductal adenocarcinoma (12), prostate cancer (13) and breast carcinoma (14). In osteoarthritis, Kizawa et al found a direct interaction between ASPN and TGF-β.…”
Section: Introductionmentioning
confidence: 99%
“…The overexpression of PACE4 in prostate cancer has been documented; however, no correlations with clinical parameters, such as Gleason grading, have been reported (6,13,14). New molecular markers with relevance to prostate cancer progression should show a positive correlation with the established histologic prognostic indicator, that is, Gleason grading, to be considered of prognostic usefulness.…”
Section: Resultsmentioning
confidence: 99%
“…19,27 Apart from PCSK9, which plays a critical part in the regulation of lipid homeostasis, 28 other PCs have been poorly characterized in cardiovascular diseases, especially in comparison with their well-documented functions in cancers. PCSK6 involvement in prostate cancer has been extensively studied, the protein itself proposed as a serum biomarker, 29 and even a selective PCSK6 inhibitor with antiproliferative effects on prostate cancer cells was recently developed. 30 It has been suggested that Furin and PCSK5 modulate inflammatory responses, 31 regulate membrane-type MMPs and integrin-processing in atherosclerosis, 32 whereas PCSK7 and PCSK2 have been detected in vascular SMCs and linked to myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%